Diverse Immunomodulatory Effects of Individual IFNα Subtypes on Virus-Specific CD8+ T Cell Responses - Dickow, Julia; Francois, Sandra; Kaiserling, Rouven-Luca; Malyshkina, Anna; Drexler, Ingo; Westendorf, Astrid Maria; Lang, Karl Sebastian; Santiago, Mario L.; Dittmer, Ulf; Sutter, Kathrin (Frontiers in Immunology, 2019)
Clinical administration of Interferon α (IFNα) resulted in limited therapeutic success against some viral infections. Immune modulation of CD8+ T cell responses during IFNα therapy is believed to play a pivotal role in promoting viral clearance. However, these clinical studies primarily focused on IFNα subtype 2. To date, the immunomodulatory roles of the remaining 10-13 IFNα subtypes remains poorly understood, thereby precluding assessments of their potential for more effective treatments. Here, we report that virus-specific CD8+ T cell responses were influenced to various extents by individual IFNα subtypes. IFNα4, 6 and 9 had the strongest effects on CD8+ T cells, including antiproliferative effects, improved cytokine production and cytotoxicity. Interestingly, augmented cytokine responses were dependent on IFNα subtype stimulation of dendritic cells (DCs), while antiproliferative effects and cytotoxicity were mediated by IFNAR signaling in either CD8+ T cells or DCs. Thus, precise modulation of virus-specific CD8+ T cell responses may be feasible for specific antiviral immunotherapies through careful selection and administration of individual IFNα subtypes.